On periodic solutions of countable systems of linear and quasilinear difference equations with periodic coefficients - Samoilenko, M. V.; Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We present conditions for the existence of periodic solutions of linear difference equations with periodic coefficients in spaces of bounded number sequences. In the case where the generating linear equation has a unique periodic solution, we indicate sufficient conditions for the existence of a periodic solution of a quasilinear difference equation.